The Healing Potential of Transcendental Meditation - Alexander Paikada (Journal of Dharma, 1977)
In our times prayer or meditation is a topical subject about which too much is written though neither the authors nor the readers have any direct experience of it. It eludes them even though they are after it. Some of the authors pretend to be masters in the art of meditation and try to theorise too much and impose it on average readers who are in search of peace and solitude. But the author of the Healing Potential of Transcenden- tal Meditation, Una Kroll is an exception. She has no such pretentious. Her book is an important addition to the literature on transcendental meditation, the wonderful yogic experience of the privileged few. It is a Christian interpretation of the yogic experience.